An Eccentric Binary with a Misaligned Circumbinary Disk - Hu, Zhecheng; Zhu, Wei; Dai, Fei; Chen, Ping; Huang, Yang; Fang, Min; Post, Richard S. (Astrophysical journal. Letters, 2024)
We present spectroscopic and photometric observations of Bernhard-2, which was previously identified as a candidate system that hosts a misaligned circumbinary disk. Our spectroscopic measurements confirm that Bernhard-2 indeed contains an eccentric ( e = 0.69 ± 0.08) binary and thus that the periodic variability in the photometric light curve is best explained by the occultation by the misaligned circumbinary disk. By modeling the spectral energy distributions at different phases, we infer the masses of the two binary components to be ∼1.1 M ⊙ and ∼0.9 M ⊙ , respectively. The system age is determined to be ≲20 Myr by combining the stellar isochrone model with lithium abundance. Our new photometric observations show clear deviations from the model prediction based on the archival data, suggesting ongoing precession of the circumbinary disk. The H α line of Bernhard-2 also shows an inverse P-Cygni profile at epochs close to the pericenter passage, which could be attributed to the pulsed accretion around the pericenter. Bernhard-2 therefore closely resembles the well-studied KH 15D system. Further detailed observations and studies of such rare systems can provide useful information about disk physics and evolution.